A parallel Viterbi decoding algorithm - Reeve, J. S. (Concurrency and computation, 2001)
In this paper we express the Viterbi algorithm as a matrix–vector reduction in which multiplication is replaced by addition and addition by minimization. The resulting algorithm is then readily parallelized in a form suitable for implementation on a systolic processor array. We describe the algorithm for Bose–Chaudhuri–Hocquenghem (BCH) codes which have a task graph with its valence restricted to four inputs and four outputs. The method is also applicable to convolution codes, but the complexity of the task graph increases with the number of input bits for these codes. Results for BCH codes are given for two general purpose parallel machines, an IBM SP2 and a Meiko CS2. Copyright © 2001 John Wiley & Sons, Ltd.